Immunopathogenesis of alzheimer's disease, parkinson's disease, and other neurodegenerative diseases - Kumar S.; Shukla A.K.; Yadav V.K.; Srivastava A.; Dwivedi D.; Singh S.P. (My University, 2025)
Neurodegenerative diseases are categorized mostly by protein deposits or known hereditary mechanisms, despite recent studies showing overlap and intraindividual variations in these symptoms. A synergistic interaction between pathological proteins advises extensive pathogenic pathways. Animal models and other studies have uncovered the fundamental mechanisms underlying neurodegeneration and cell death, opening up new avenues for future prevention and therapy plans. A multidomain therapy approach that emphasizes the underlying reasons why diseases alike Parkinson's, Alzheimer's, etc. occur. Neurodegenerative diseases like Parkinson's disease (PD) and Alzheimer's disease (AD) are becoming far more common in the Western world. Neuronal inflammation, gut microbiota, extracellular misfolded protein accumulation, hallmarks of various neurodegenerative nephropathies, and failure of the systemic and cerebral immune systems are some of the elements that affect the immunopathogenesis of neurodegenerative diseases. Deficits in the ubiquitin proteasome autophagy system, abnormal protein dynamics brought on by oxidative stress and free radical formation, mitochondrial dysfunction, impaired bioenergetics, neurotrophins dysfunction, "neuroinflammatory" processes, and (secondary) distractions of neuronal Golgi apparatus and axonal passage are some of the fundamental mechanisms that contribute to immunopathogenesis. Long-term cooperation between these interconnected systems results in programmed cell death. In this review, we discussed every idea and hypothesis that have been put up on the pathophysiology of neurodegenerative disorders. © 2024, Bentham Books imprint. All rights reserved.